Transformation of Adaptive Learning Models in Islamic Religious Education in the Digital Era - Muhamad Wijaksono; Fitri Hilmiyati; Yahdinil Firda Nadirah; Deni Iriyadi; Wasehudin, Wasehudin; Aas Siti Sholichah (Scidac Plus, 2026)
The transformation of learning in the digital era demands a change in approach to the educational process, including in Islamic Religious Education (PAI). A common problem in PAI learning is the use of conventional methods, which are too uniform, teacher-centered, and pay little attention to the abilities, interests, and learning styles of each student. The purpose of this study is to explore ideas and changes in adaptive learning modules for PAI subjects in the digital era in an effort to improve the effectiveness of more contextual and individualized learning. This study used a qualitative research method with a literature review approach. Various scientific literature, books, and research results related to adaptive learning and its implementation in Islamic education were analyzed. The results show that adaptive learning modules enable PAI materials to be tailored to students' learning needs. This can be done using digital technologies such as learning data analysis, Learning Management System (LMS) platforms, and artificial intelligence. These modules provide students with the opportunity to learn according to their capacity, pace, and learning characteristics. In addition, adaptive modules help learning become more interactive, reflective, and relevant to the challenges of the digital era, while maintaining the moral and spiritual values ​​of Islamic education. The implementation of adaptive modules in Islamic Religious Education subjects in the digital era can improve the quality of learning, increase student engagement, and encourage a more inclusive, effective, and student-oriented learning process.